Who watch the eggs? Assessing the portuguese agricultural credit co-operatives governance - Cabo, Paula (2013)
In recent years the importance of corporate governance has rising new attention, as the 2008 financial crisis illustrates. Co-operatives, like investor-owned firms, have not remained untouched by the recent corporate governance scandals nor by the development of codes of good practice. This paper intends to analyse CCAM governance and assess its efficacy in disciplining management. Hence, using data from 1995-2009 period, and multinomial logit models we analyse the relation between CCAM performance and the several control mechanisms operating within SICAM. Overall, results show that the internal governance mechanisms are not related to the CCAM performance, which indicates potential weakness of the CCAM internal control mechanisms. On the other hand, external governance mechanisms are related to CCAM operational and cost efficiency indicators, thus, demonstrating the superiority of theses mechanism in disciplining CCAM management. Plus, the results show up the importance of the supervision task of Central CCAM in the performance of the associates.